2012
DOI: 10.1002/cncr.27382
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 results from Radiation Therapy Oncology Group Study 0537

Abstract: Purpose This phase II component of a multi-institutional phase II/III randomized trial assessed the feasibility and preliminary efficacy of acupuncture-like transcutaneous electrical nerve stimulation (ALTENS) in reducing radiation-induced xerostomia. Methods Head and neck cancer patients who were 3–24 months from completing radiotherapy ± chemotherapy (RT±C) and experiencing xerostomia symptoms with basal whole saliva production ≥0.1 ml/min and without recurrence were eligible. Patients received twice weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…To date, many therapeutic agents including saliva substitutes [26], intensity-modulated radiotherapy [27,28], pilocarpine [29,30,31,32], acupuncture [33,34], and amifostine [35,36] had been available to alleviate radiation-induced xerostomia, but they rarely had curable effects or were even controversial regarding the safety of their use. So, the best method to treat postradiation xerostomia would be to choose preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many therapeutic agents including saliva substitutes [26], intensity-modulated radiotherapy [27,28], pilocarpine [29,30,31,32], acupuncture [33,34], and amifostine [35,36] had been available to alleviate radiation-induced xerostomia, but they rarely had curable effects or were even controversial regarding the safety of their use. So, the best method to treat postradiation xerostomia would be to choose preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-institutional, 48 patient, phase II trial that followed showed similar efficacy with a positive treatment response in 86% of patients using the self-reported XeQOLS surveys to evaluate response at baseline and 6 months post-treatment. 5 Eligibility for ALTENS was limited to those within 24 months of completing chemoradiation. 5 In a 148 patient, phase III multi-institutional randomised study comparing ALTENS with pilocarpine therapy, Wong et al 6 found ALTENS ALTENS therapy success using a commercially available unit 8 years post-radiation for xerostomia ALTENS therapy success using a commercially available unit 8 years post-radiation for xerostomia was just as efficacious as pilocarpine but produced significantly less grade 3 or less adverse events (20·8-61·6%).…”
Section: Discussionmentioning
confidence: 99%
“…5 Eligibility for ALTENS was limited to those within 24 months of completing chemoradiation. 5 In a 148 patient, phase III multi-institutional randomised study comparing ALTENS with pilocarpine therapy, Wong et al 6 found ALTENS ALTENS therapy success using a commercially available unit 8 years post-radiation for xerostomia ALTENS therapy success using a commercially available unit 8 years post-radiation for xerostomia was just as efficacious as pilocarpine but produced significantly less grade 3 or less adverse events (20·8-61·6%). A secondary analysis of this study using the RTOG-modified University of Washington Head and Neck Symptom Score to assess overall health-related quality of life demonstrated consistently lower scores, indicating better function, for patients randomised to the ALTENS arm compared with those randomised to pilocarpine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations